2017
DOI: 10.1093/carcin/bgx042
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Opisthorchis felineus induces intraepithelial neoplasia of the biliary tract in a rodent model

Abstract: The liver fluke Opisthorchis felineus is a member of the triad of epidemiologically relevant species of the trematode family Opisthorchiidae, and the causative agent of opisthorchiasis felinea over an extensive range that spans regions of Eurasia. The International Agency for Research on Cancer classifies the infection with the liver flukes Opisthorchis viverrini and Clonorchis sinensis as group 1 agents and a major risk factor for cholangiocarcinoma. However, the carcinogenic potential of the infection with O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 36 publications
3
88
0
1
Order By: Relevance
“…It should be noted that the animals were processed as part of normal work of the slaughterhouse. O. viverrini and O. felineus were obtained as previously described [3,4]. In brief, metacercariae of Opisthorchis species were obtained from naturally infected cyprinoid fish in Khon Kaen province, Thailand or from naturally infected fish ( Leuciscus idus ) in the Ob River near the city of Novosibirsk, Siberia Russia, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted that the animals were processed as part of normal work of the slaughterhouse. O. viverrini and O. felineus were obtained as previously described [3,4]. In brief, metacercariae of Opisthorchis species were obtained from naturally infected cyprinoid fish in Khon Kaen province, Thailand or from naturally infected fish ( Leuciscus idus ) in the Ob River near the city of Novosibirsk, Siberia Russia, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, metacercariae of Opisthorchis species were obtained from naturally infected cyprinoid fish in Khon Kaen province, Thailand or from naturally infected fish ( Leuciscus idus ) in the Ob River near the city of Novosibirsk, Siberia Russia, respectively. The fish were digested with pepsin-HCl [3]. Fifty metacercariae were used to infect hamsters ( Mesocricetus auratus ) and three months after infection, the animals were euthanized and adult O. viverrini or O. felineus flukes recovered from their bile ducts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is presumably because the domestic dog-livestock cycle associated with E. granulosus is relatively easier to interrupt (by worming dogs, preventing dogs from scavenging domestic animal remains at abattoirs and in the fields, and efforts at meat inspection), than the predominantly sylvatic E. multilocularis cycle (foxes-rodents). Not only is the prevalence of E. multilocularis apparently not decreasing, but the distribution of the parasite seems to be spreading in some areas of northern Europe and it seems to be emerging, becoming identified in some areas previously not considered particularly associated with the parasite, in other regions of the world (Conraths & Deplazes, 2015;Davidson, Romig, Jenkins, Tryland, & Robertson, 2012;Gottstein et al, 2015;Vuitton et al, 2015). For example, a case-finding study noted an increase in the prevalence of human AE in Switzerland over a 50-year period from 1956 to 2005, which could not be explained by improved diagnosis; the authors suggested that this change in prevalence may be associated with a rising fox population, which, in turn, is associated with a successful antirabies vaccination program (Schweiger et al, 2007).…”
Section: Specific Example Parasites: the Transition From Neglected Pomentioning
confidence: 99%